Da'wah Strategy for Position Matters of Sabah State Islamic Religion (JHEAINS) Part of Tuaran towards Muallaf Group - Nurshaiera Binti Jusup (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
Strategy is a business or process in various ways that are carried out to achieve a pre-planned goal. At the same time, da'wah is all activities and activities inviting people to change from a situation that contains non-Islamic values to Islamic values. The Sabah State Islamic Affairs Department, is an agency for the State Government Office whose role is to monitor and carry out da'wah activities in the land of Sabah. This research aimed to discover the da'wah strategy carried out by the Department of Islamic Religion of the State of Sabah, the Tuaran Section, towards converts through the da'wah methods and approaches displayed by the da'i from this agency. The method used in this research is the descriptive method. Because the main objective of the research is to describe and explain the da'wah strategy used by the Department of Islamic Affairs in the State of Sabah, the Tuaran Section, against true converts, this research was conducted by taking the following steps: determining the research location, research method, determining the type and source of data, data collection techniques, and finally analyzing the data. The study results showed that the da'wah activities of the Department of Islamic Affairs of the State of Sabah (JHEAINS) in the Tuaran section had not provided optimal da'wah efforts. This is due to insensitivity in management and control on the part of the da'i, as well as a lack of appreciation for the vision and mission of JHEAINS in every individual engaged in carrying out da'wah efforts against converts. Based on these findings, it can be concluded that the da'wah strategy of the Department of Islamic Affairs of the State of Sabah (JHEAINS) in the Tuaran section has not been able to attract many people who have not accepted Islam to Islam. Therefore, JHEAINS must further improve its strategy and reactivate the implementation of its methods and approaches in determining the faith of converts.